Effects of nanoparticle size on the interaction between zinc oxide nanoparticles and bovine serum albumin. Issue 4 (3rd March 2020) - Wang, Liwei; Liang, Tingting; Ma, Jun; Sun, Liqian; Yang, Congcong; Meng, Liqiang; Liang, Taigang; Li, Qingshan
Abstract : Communicated by Ramaswamy H. Sarma